Comprehensive Characterization of Tuber maculatum, New in Uruguay: Morphological, Molecular, and Aromatic Analyses - Kuhar, Francisco; Tejedor-Calvo, Eva; Sequeira, Alejandro; Pelissero, David; Cosse, Mariana; Donnini, Domizia; Nouhra, Eduardo (Journal of fungi (Basel), 2024)
Although only a few species of Tuber account for the major truffle sales volume, many species that are not considered delicacies are finding their way to the market, especially in regions where the traditionally appreciated ones do not occur. This is the case for whitish truffles. Specimens of whitish truffles were collected in pecan (Carya illinoinensis) orchards in Uruguay in October 2021. Morphological and molecular methods were used to characterize and assess their identity as Tuber maculatum Vittad. An SPME extraction of volatile compounds and GC–MS analyses were performed to characterize the aromatic profile of these specimens and evaluate their potential applications. Among the 60 VOCs detected, 3-octenone (mushroom odor), 3-octanol (moss, nut, mushroom odor), and 2H-pyran-2-one (no odor), followed by octen-1-ol-acetate (no odor) and 2-undecanone (orange, fresh, green odor) were the major compounds in T. maculatum fruiting bodies. The attributes of exotic edible mushrooms of commercial value in the region are highlighted. In particular, this work emphasizes the characteristics of truffles as a byproduct of pecan cultivation.